151 reputation
1212
bio website
location
age
visits member for 2 years, 5 months
seen Oct 19 at 2:19

Jul
2
awarded  Curious
Mar
11
accepted Prove that $\bigcup_{n=2}^{\infty} [1/n, 1 - 1/n] = (0, 1)$
Mar
11
asked Prove that $\bigcup_{n=2}^{\infty} [1/n, 1 - 1/n] = (0, 1)$
Dec
8
awarded  Critic
Nov
28
accepted Solve $z^4 + 4 = 0$
Nov
28
comment Solve $z^4 + 4 = 0$
That $e^{-i \pi} = 1$ is exactly what I was missing. I went and tried to blindly solve it without taking that into account. Thank you and Stahl for pointing it out.
Nov
28
asked Solve $z^4 + 4 = 0$
Oct
20
revised Proving $mn = 0$ implies $m = 0$ or $n=0$ for all $m, n \in \mathbb{N}$ using Peano Axioms
added 25 characters in body
Oct
20
accepted Proving $mn = 0$ implies $m = 0$ or $n=0$ for all $m, n \in \mathbb{N}$ using Peano Axioms
Oct
20
comment Proving $mn = 0$ implies $m = 0$ or $n=0$ for all $m, n \in \mathbb{N}$ using Peano Axioms
$m = k^+$ and $n = l^+$ for some $k, l \in \mathbb N$ by the third axiom. That's a nice and straightforward proof. Thank you.
Oct
20
asked Proving $mn = 0$ implies $m = 0$ or $n=0$ for all $m, n \in \mathbb{N}$ using Peano Axioms
Jul
11
revised Why is the Fibonacci ratio though a decreasing function, it is alternating and decreasing?
Improved formatting
Jul
11
suggested suggested edit on Why is the Fibonacci ratio though a decreasing function, it is alternating and decreasing?
Jul
3
comment Proof of $A\cap(B\cup C) = (A\cap B)\cup(A\cap C)$
For proofs like this, using the definition of set operations (which are mostly) and using rules of inference always worked for me.
Jun
18
awarded  Popular Question
May
9
comment Simplify $(p)(\frac{1}{2}(2p-1)^n) + (1-p)(-\frac{1}{2}(2p-1)^n)$ to $\frac{1}{2}(2p-1)^{n+1}$
Um, I guess you're right. Now I know I have to be more careful with signs. I was cancelling out both $p$.
May
9
comment Simplify $(p)(\frac{1}{2}(2p-1)^n) + (1-p)(-\frac{1}{2}(2p-1)^n)$ to $\frac{1}{2}(2p-1)^{n+1}$
Your answer is very detailed too, and I feel embarrassed for missing that $(-1)$. Have an upvote.
May
9
accepted Simplify $(p)(\frac{1}{2}(2p-1)^n) + (1-p)(-\frac{1}{2}(2p-1)^n)$ to $\frac{1}{2}(2p-1)^{n+1}$
May
9
comment Simplify $(p)(\frac{1}{2}(2p-1)^n) + (1-p)(-\frac{1}{2}(2p-1)^n)$ to $\frac{1}{2}(2p-1)^{n+1}$
Thank you for the clarification. I'll accept Maazul's (since he answered first). I already upvoted yours.
May
9
comment Simplify $(p)(\frac{1}{2}(2p-1)^n) + (1-p)(-\frac{1}{2}(2p-1)^n)$ to $\frac{1}{2}(2p-1)^{n+1}$
The answers show me I indeed had that problem. I kinda feel bad for making this question.